2019
DOI: 10.5194/acp-19-9641-2019
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal differences in formation processes of oxidized organic aerosol near Houston, TX

Abstract: Abstract. Submicron aerosol was measured to the southwest of Houston, Texas, during winter and summer 2014 to investigate its seasonal variability. Data from a high-resolution time-of-flight aerosol mass spectrometer (HR-ToF-AMS) indicated that organic aerosol (OA) was the largest component of nonrefractory submicron particulate matter (NR-PM1) (on average, 38 % ± 13 % and 47 % ± 18 % of the NR-PM1 mass loading in winter and summer, respectively). Positive matrix factorization (PMF) analysis of the OA mass spe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 71 publications
2
29
0
Order By: Relevance
“…Most previous studies on pON quantification are based on filter measurements using gas chromatography (GC) (O'Brien et al, 1995) and Fourier transformed infrared (FTIR) spectroscopy (Blando et al, 1998). Online measurement techniques -e.g., thermal dissociation-laser-induced fluorescence (TD-LIF) (Day et al, 2002), thermal dissociation-cavity ring-down spectroscopy (TD-CRDS) (Thieser et al, 2016) and thermal dissociation-cavity attenuated phase shift spectroscopy (TD-CAPS) (Sadanaga et al, 2016) -were also used to characterize pON in the atmosphere. The principle is to convert pON to NO 2 first and then to subtract ambient NO 2 from the total NO 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most previous studies on pON quantification are based on filter measurements using gas chromatography (GC) (O'Brien et al, 1995) and Fourier transformed infrared (FTIR) spectroscopy (Blando et al, 1998). Online measurement techniques -e.g., thermal dissociation-laser-induced fluorescence (TD-LIF) (Day et al, 2002), thermal dissociation-cavity ring-down spectroscopy (TD-CRDS) (Thieser et al, 2016) and thermal dissociation-cavity attenuated phase shift spectroscopy (TD-CAPS) (Sadanaga et al, 2016) -were also used to characterize pON in the atmosphere. The principle is to convert pON to NO 2 first and then to subtract ambient NO 2 from the total NO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, pON were also quantified using a highresolution aerosol mass spectrometer (HR-AMS) mainly based on the differences of fragmentation patterns between pON and inorganic nitrate (Xu et al, 2015b;Farmer et al, 2010;Kortelainen et al, 2017;Ng et al, 2017). The "PMF method" and "NO x method" are the two most commonly used methods for pON quantification (Fry et al, 2013;Xu et al, 2015b;Yu et al, 2019;Dai et al, 2019). The PMF method, which combines organic and inorganic fragments in positive matrix factorization (PMF) analysis, was able to identify organic aerosol factors that showed a largely different NO + / NO + 2 ratio from pure ammonium nitrate (AN).…”
Section: Introductionmentioning
confidence: 99%
“…Relatedly, Zhao et al (2017) revealed the non-linear increasing relation of SOA production as a function of the NMOG-to-NO x precursors ratio (NMOG being the non-methane organic gases emitted by vehicles, which include VOCs), entailing a coupled reduction of both pollutants has to be addressed in order to reduce SOA concentrations. As well as this, Dai et al (2019) highlighted the differences in conditions of liquid water content (LWC), meteorological variables, and OX concentrations for the SOA to take the aqueous-phase chemistry or photochemistry pathways depending on the season. Despite that, there is a need for further investigation about the oxidation state of OA in consideration of different seasons, years, meteorological scenarios and precursor levels to characterize these findings in an urban background site in the WMB.…”
Section: Introductionmentioning
confidence: 86%
“…Black carbon (BC) concentrations were measured with 1 min time resolution by a multi-angle absorption photometer (MAAP, Thermofisher Model 5012). PM 1 concentrations were measured by summing up the particle size number distribution (ranging 12-470 nm) measured by a scanning mobility particle sizer (SMPS, TSI 3080) with 5 min time res-olution and converted to mass concentrations by means of the composition-dependent aerosol density (DeCarlo et al, 2004). SO 2− 4 , NO − 3 and NH + 4 concentrations were determined in off-line PM 1 filters samples by ion chromatography and selective electrode methods.…”
Section: Additional Measurements and Instrumentationmentioning
confidence: 99%
“…Recently, pON were also quantified using high-resolution aerosol mass spectrometer (HR-AMS) mainly based on the differences of fragmentation patterns between pON and inorganic nitrate (Xu et al, 2015b;Farmer et al, 2010;Kortelainen et al, 2017;Ng et al, 2017). "PMF method" and "NO x method" are two most commonly used method for pON quantification (Fry et al, 2013;Xu et al, 2015b;Yu et al, 2019;Dai et al, 2019). The "PMF method" by combining organic and inorganic fragments in positive matrix factorization (PMF) analysis was able to identify organic aerosol factors that showed largely different NO + /NO 2 + ratio from pure ammonium nitrate (AN).…”
Section: Introductionmentioning
confidence: 99%